Pengembangan Buku Cerita Bergambar berbasis Pendekatan Deep learning pada Siswa Kelas III Sekolah Dasar - Alisa Hikma Rosida; Sumartiningsih, Sri; Haryani, Sri (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2025)
The limited availability of reading materials that suit the characteristics of students and their environment encourages the need for innovative learning media in elementary schools. Based on these problems, this study aims to develop and produce picture story books based on in-depth learning that are appropriate, interesting, and appropriate to the needs of third-grade elementary school students. The method used is Research and Development (R&D) with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The data obtained in the study were then analyzed descriptively quantitatively and qualitatively. The subjects of this study were 22 third-grade students of Kataan Elementary School. Based on the results of the study, the validation test from material experts obtained a score of 94.4% and media experts 88.8%. The results of limited trials from students obtained a score of 97.18% and teachers obtained a score of 90%. Meanwhile, the results of extensive trials from students obtained a score of 86.7% and teachers obtained a score of 90%. Thus, it can be concluded that this picture story book based on in-depth learning is very suitable for use to support literacy activities in elementary schools.